Research on characteristics of thermoelectric generator with integrated muffler and catalytic converter - Xun Liu (Elsevier, 2022)
Automobile exhaust contains a large amount of heat loss, which has a high potential for energy saving. In order to recover the heat in the exhaust gas and improve the compatibility of thermoelectric generator (TEG), muffler and catalytic converter, an integrated automobile exhaust thermoelectric generator (IATEG) integrating muffler, and catalytic converter is proposed. Research on its performance by establishing a three-dimensional model, On the basis of finite element simulation, the model’s surface temperature field, muffler transmission loss, exhaust back pressure and conversion efficiency are compared and studied when the catalytic converter is placed in the front part (A), middle part (B) and rear part (C) of the model. The results show that when the exhaust temperature is 350 °C and the inlet velocity is 30 m/s, the average surface temperature of model B is the highest, which is 291.95 °C. The exhaust back pressure of the three models is almost the same and meets the requirements of QC/T 631-2009 (15 kPa). Compared with the original muffler of the automobile, the transmission loss of the three models is greater than that of the original muffler. From the perspective of improving the conversion efficiency of NOx, the exhaust flow field distribution of the catalytic converter of Model B is more uniform and has a smaller impact on the conversion efficiency of NOx. Therefore, it is recommended that IATEG choose the structure of Model B. This article demonstrates the possibility of IATEG integrating muffler and catalytic converter in terms of performance.